(untitled) (International Journal of Environmental Sciences, 2025)
The fast development of Artificial Intelligence (AI) has seen a change in the conventional pricing mechanisms that have been introduced with adaptive, data-driven, and predictive approaches world markets. In this paper, the author presents the concept of Pricing Intelligence 2.0, devoting his attention to how the development of decision-making processes in market economies is fundamentally changed through the AI-driven stochastic models and nonlinear systems. We can model price volatility and demand changes with the help of AI-influenced strategies by relying on stochastic differential equations and large deviation theory. Examples of e-commerce, retail, and algorithmic trading case studies reflect the discontinuous threat of AI on competitive situations. Bifurcation behaviors simulation in situations of uncertainty further indicates critical thresholds, which prescribe the market regime change. In our analysis the ambivalent character of noise unfolds as a disruptor and a stimulator of strategic pricing under the stochastic resonance. The proposed study suggests a coherent framework that unifies artificial intelligence and dynamic modeling with the economic theory to enable strategic pricing in an uncertain environment and provides the directions of robust market intelligence systems in the era of intelligent algorithms.